Factor Analysis of the Distribution of Religious Denominations in Romania: Considerations for Business Administration - Iustin-Cornel Petre (Ovidius University Annals: Economic Sciences Series, 2025)
The study analyzes the distribution of religious denominations in the Romanian counties using correspondence factor analysis, exploring its implications for business management. Based on official statistical data, the research highlights the relationships between confessional structure and regional specificity, identifying the main dimensions that explain religious variation. The results show that the confessional diversity in Transylvania contrasts with the predominantly orthodox uniformity in the south and east of the country, and that religious particularities directly influence cultural values, business strategies and managerial decisions. The integration of literature emphasizes the role of religion as a shaping force in strategic planning, sustainable development and business ethics. The study contributes to an interdisciplinary understanding of the dynamics between religion and economics, providing an analytical framework for adapting organizational strategies to cultural and confessional characteristics. Findings reveal the importance of a customized approach to conducting business across regional religious distribution, promoting social inclusion and cohesion.